Exploring shRNA-based therapy to prevent chemotherapy-induced cardiotoxicity - Gómez, Carolina; Hernández Bellido, Natalia; García Mendivil, Laura; Sánchez Barat, Marcos; Paz Artigas, Laura; Ciriza, Jesús; Ordovás, Laura (Jornada de Jóvenes Investigadores del I3A, 2024)
Chemotherapy-induced cardiotoxicity is an often fatal consequence of some cancer treatments, such as anthracyclines like doxorubicin (DOXO), for which there is currently no preventive treatment. Since the cardiotoxic mechanism of DOXO is due to its action on topoisomerase 2 β (TOP2B), some studies have described the protective effects of its cardiomyocyte-specific inhibition. In this work we have develop and characterized an RNA interference (RNAi) strategy to inhibit TOP2B. Although our preliminary results show low inhibition of TOP2B in vitro, they encourage future development of more efficient shRNAs.